Model Promosi Kesehatan “JEM” Upaya Mitigasi Bahaya Kebakaran pada Anak di Wilayah Kerja Pemadam Kebakaran Ciracas - James Criony; Nina Nina; Astrid Novita (Poltekkes Kemenkes Padang, 2024)
Public awareness in mitigating the dangers of fire is still lacking, as can be seen from the high number of fire incidents. The DKI Fire Department recorded 9,200 fires in the 2019-2023 period. Fire mitigation requires a learning model. The Fire Department does not yet have a fire mitigation health promotion model. Based on this, the JEM (Mitigation Effectiveness Bridge) model was formulated, which is a fire mitigation learning model. This model was built in several stages using the ADDIE method. Method: Mixed method research design with 2 types of research studies. Qualitative study designing a health promotion model and developing fire mitigation media; Quantitative studies test the effectiveness of media. Qualitative study focus group discussion respondent 4 experts in Health Promotion, K3, Children's Education and media. ; Quantitative quasi-experiment study with respondents of 30 children aged 8-12 years. Results: qualitative study output JEM Model and audio-visual media for fire mitigation. Quantitative Study Media effectiveness test, sample paired t test results showed differences in children's abilities in mitigating fire disasters, pretest = 4.6333, posttest = 9.6667. There is an increase in children's abilities in knowledge of fire hazard mitigation Sig (2 tailed) < 0.05. Conclusion: The JEM Health Promotion Model has proven to be effective and easy for school children to understand regarding fire disaster mitigation.